Stora Enso’s Usage of Child Labour in Pakistan : A Case Study - Kalajoki, Iivo Taneli (My University, 2025)
In 2014, Stora Enso, a Finnish-Swedish paper and packaging company was revealed to have been using child labour as part of its operations in Pakistan. This paper analyses what happened through the lens of corporate criminology, a strain of criminology concerned with the crimes of powerful organisations. The paper creates a better understanding of both the particular and the generic causes that lead to the events of the case. The method of analysis is the case study. The theoretical framework of the paper consists of three concepts, those being state-corporate crime, regimes of permission and organisational legitimacy. The study found that the case is part of a larger pattern of delictual corporate behaviour and liability avoidance. Even though Stora Enso’s conduct was objectively deliberate as well as reprehensible, it wasn’t portrayed as criminal, and no legal action was taken. This is indicative of large regulatory gaps. The public reception to the case is also noteworthy, as it on one hand forced Stora Enso to make a change in its conduct, but on the other hand framed the issue as a rogue “moment of rupture”, rather than the symptom of a larger systemic issue. As remedial measures, the paper suggests adapting a stricter form of shareholder liability, which would encourage corporations to prioritise more sustainable and ethical practises. Legally enforced CSR programs, as well as better international regulations would also go a long way to address the issues. Lastly, NGOs and the media need to understand their role in constructing narratives on organisational legitimacy and pay more attention to how they frame cases such as this.

Vuonna 2014 paljastui, että suomalais-ruotsalainen paperi- ja pakkausvalmistaja Stor-Enso oli käyttänyt lapsityövoimaa osana liiketoimintaansa Pakistanissa. Tämä artikkeli analysoi tapahtunutta yhteisökriminologian näkökulmasta. Yhteisökriminologia on kriminologian osa-alue, joka tutkii vaikutusvaltaisten organisaatioiden rikollisuutta. Artikkeli luo käsityksen niistä tapauskohtaisista ja yleisistä syistä, jotka johtivat tapaukseen. Analyysin metodina toimii tapaustutkimus. Tutkimuksen teoreettisen viitekehyksen muodostavat kolme teoriaa, jotka ovat valtioyhteisörikollisuus, sallivuuden regiimit sekä organisaatiolegitiimiys. Tutkimuksessa ilmenneiden havaintojen perusteella tapaus kertoo laajemmasta yhteisörikollisuuden ja vastuunvälttämisen kuviosta. Siitä huolimatta, että Stora Enson toiminta oli objektiivisesti katsottuna sekä tahallista että tuomittavaa, ei tapahtumia ikinä kuvattu rikoksina, eikä niistä seurannut minkäänlaisia laillisia seuraamuksia. Tämä kielii laajojen sääntelyaukkojen olemassaolosta. Yleinen mediareaktio on myös pantava merkille, sillä se yhtäältä pakotti Stora Enson muuttamaan toimintaansa, mutta toisaalta muotoili asian siten, että tapaus nähtiin satunnaisena ”purkaushetkenä”, sen sijaan että sitä oltaisiin käsitelty systemaattisten ongelmien oireena. Ratkaisuna edellä kuvattuihin ongelmiin, tutkielma ehdottaa mm. tiukempaa osakkeenomistajien vastuulainsäädäntöä, joka kannustaisi yhtiöitä kohti kestävämpiä ja eettisempiä toimintamalleja. Kansainvälistä ja kansallista CSR-toimia sekä tiukempaa valvontaa edistävää lainsäädäntöä olisi lisättävä. NGO-järjestöjen ja median tulisi myös ymmärtää paremmin roolinsa yleisen narratiivin rakentajina, ja kiinnitettävä huomiota siihen, miten ne käsittelevät tällaisia tapauksia.
Keywords: Corporate crime, Corporate social responsibility, Human rights, Organisational theory ihmisoikeudet, organisaatiorikokset, organisaatioteoriat, yritysvastuu